Images of the divine : the theology of icons at the Seventh Ecumenical Council - Giakalis, Ambrosios (Studies in the history of Christian traditions ;, 2005)
"This book, newly revised and updated, examines the Eastern Church's theology of icons chiefly on the basis of the acta of the Seventh Ecumenical Council of 787." "The political circumstances leading to the outbreak of the iconoclast controversy in the eighth century are discussed in detail, but the main emphasis is on the theological arguments and assumptions of the council participants. Major themes include the nature of tradition, the relationship between image and reality, and the place of Christology." "Ultimately the argument over icons was about the accessibility of the divine. Icons were held by the iconophiles to communicate a deifying grace which raised the believer to participation in the life of God"--Jacket